Poetry and history in Scorza’s narrative - Ruiz Ledesma, César Vladimir (2022)
In the next article I analyze the poetic figures that Manuel Scorza uses in his fiction writing. For instance, just paying attention to the title of the Silent War we can find some clues. For instance, there is in Drums for Rancas a verse technique called alliteration, that makes the title resonant. Then, I will talk about how this poetic style serves to Scorza for rewriting the official history of Peru and for depict the thought of the Andes or the Andean epistemology. He achieves the first by comparing the Independence Day with the Peruvian Army that kills peasants and he achieves the second by focusing on nature and myth.